Kinetics of Oil-in-Water Emulsion Stabilization using Lecithin and Biosilica - Lanny Sapei; Olivia Poppy Damayanti; Liliana Liliana (Department of Chemical Engineering, Universitas Gadjah Mada, 2019)
Oil-in-water (O/W) emulsion has been widely used in food emulsions such as mayonnaise, dressings, and sauces. However, O/W emulsion is inherently thermodynamically unstable and easily destabilizes with time. Synthetic polymeric emulsifiers have been commonly used to stabilize these emulsions. However, those synthetic emulsifiers may induce obesity and other unexpected side-effects. In this experiment, bio-emulsifier mixtures consisting of soy lecithin and bio-silica were combined to stabilize the o/w emulsion in order to obtain more healthful food emulsions with acceptable quality. Lecithin concentrations were varied from 0.05-1.5% and concentrations of pure bio-silica particles derived from rice husks were in the range of 0.5-3%. The effects of the concentrations of these emulsifier mixtures on the O/W emulsions stability were studied. Additionally, the effects of storage temperatures on the O/W emulsions stability in the presence of both lecithin and bio-silica were investigated. The kinetics parameters of resulting O/W emulsions were analyzed using zero and first order kinetic models. In general, emulsions destabilized with time and followed the first order kinetic model. The destabilization rates of emulsions in the presence of emulsifier mixture would decrease by approximately 25-50% as compared to the destabilization rates of emulsions in the presence of lecithin or bio-silica as their sole emulsifier. Variations of lecithin and bio-silica concentrations in the emulsifier mixtures were not significant to the O/W emulsions stabilization. Furthermore, destabilization rate constants of O/W emulsions stored at the refrigerated temperature were 2 times lower than those stored at room temperature.